(untitled) (Revista "Boletín el Conuco", 2021)
The growth of the economy has been the trigger for many changes at the structural and financial level of the companies, where the search for the creation of value by them became a main objecti- ve and thanks to this, a fundamental role was as-signed to the financial area within the companies being that “finances sought the creation of value, putting into operation new investment schemes, financial and operational leverage” (Crivellini, 2010, párr. 3). For this reason, it is necessary to carry out the valuation for which it is necessary to resort to the three-year history of Financial Statements, which in turn will allow to determine the actual situation of liquidity and the operational results of thisentity. , to apply the discounted free cash flow method, which is suitable for companies that are not listed on the stock exchange and with which you can know the current situation, if it is favo- rable to exhibit before investors, future partners or buyers and if the Management was optimal.